Research assistance and publication of class action research results for junior high school teachers - Yuni Pantiwati; Samsun Hadi; Endrik Nurrohman; Tasya Novian Indah Sari (Journal of Community Service and Empowerment, 2023)
Teacher competence in carrying out Classroom Action Research (CAR) and presenting CAR results in the form of scientific work is a demand as well as a need in improving the quality of learning and teacher professionalism. The Chairperson of the MGMP IPA Malang city said that teachers' abilities and skills in conducting research still needed to be improved, especially for CAR research. The purpose of community service activities is to assist, direct, and collaborate with teachers in classroom action research activities and publish the results. The activities were carried out from June to December 2022. The mentoring activities were carried out in 3 Junior High Schools in Malang represented by one science teacher. Assistance is carried out online and offline. Assistance methods by means of lectures, brainstorming, discussions. The results of the mentoring activities resulted in 3 proposals and a CAR final report with different topics and CAR articles. Teachers have shown an increase in the ability to compile, apply and report CAR and scientific publications in the form of articles after the pre and post tests were carried out.